When legitimate claims collide: communities, media and dialogue - Grinell, Klas (Museum and Society, 2015)
This paper discusses the exhibition Jerusalem at the Museum of World Culture (MoWC) in Gothenburg, Sweden. The exhibition mixes photographs of LGBTQ (LesbianGayBiTransQueer) persons in Jerusalem, with quotes from the three Abrahamitic Holy Scriptures condemning homosexual activities and behaviours. MoWC held dialogues with religious persons. Although no-one wanted to stop the exhibition, many were critical of the artist’s mixing of Holiness and Nudity/Sexuality. The Museum was criticized for bending to fundamentalist pressure, assuming that it had plans to stop the exhibition, and a media debate on censorship and freedom of speech followed. This paper analyzes the situatedness of MoWC, and its discursive belonging. How can a state governed institution deal with legitimate and opposing claims, and counter both heteronormativity and islamophobia? What discourses is the Museum institution inscribed in? What power relations follow from that? Is it, due to historic, bureaucratic, and cultural legacies, tied to certain positions and affiliations in the public space?